Enhancing digital marketing of MSMEs through comprehensive photography training in Hendrosari Village, Gresik - Risma Ayu Kinanti; Arum Indiharwati; Abdul Hakam; Ajrina Valentine Marhadyta; Warti'ah Warti'ah (University of Merdeka Malang, 2024)
MSMEs in Hendrosari Village have been struggling with digital marketing due to a lack of expertise in creating compelling visual content, which has led to poor online visibility and stagnating sales. Additionally, these businesses face challenges in keeping up with ever-evolving digital trends, limited access to affordable digital tools, and insufficient training opportunities, further hampering their ability to compete in a growing online marketplace. An extensive photography training program was launched, aimed at equipping 15 MSMEs in Hendrosari Village, the target groups of this service initiative, with essential skills in lighting, composition, and post-processing techniques. This program aims to enhance their visual content creation capabilities, helping them improve their online presence and market competitiveness. The program combined theoretical lessons with hands-on practice, allowing participants to immediately apply what they learned. The community service team conducted observations and interviews before and after the training to assess changes in product photo quality and the impact on sales. The average photo quality assessment score increased from 3 to 4.5. In addition, some participants reported a 15 percent increase in income after learning new photography techniques. Based on the evaluation process, it shows that the photography training has strong potential to improve the competitiveness of MSMEs in Hendrosari village, which can inspire similar programs in other areas.Â